Understanding younger generations’ perceived service quality, value, and satisfaction in coffee shops in Kota Bharu, Kelantan. An empirical analysis of young generations’ perceptions / Putri Nur Ania Mohd Ali … [et al.] - Mohd Al, Putri Nur Ania; Mohamed Rani, Zaharah; Ahmad, Khairun Najiah; Abas, Siti Aisah; Ahmad, Nurul Aziah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
This research investigates the perception of service quality, value, and satisfaction among younger generations visiting coffee shops in Kota Bharu, Kelantan. The study aims to understand their preferences and intentions, as these factors greatly influence young generation’s satisfaction. The authors employed the DINEERV model's five key factors for assessing perceived service quality. The main goal of this research is to gain insights into how young generations perceive, feel satisfied with, and intend to behave towards coffee shops in Kota Bharu, Kelantan. Kelantan, like many regions, faces unique challenges and trends among its young population. These challenges may include shifts in consumer preferences, economic factors, or cultural influences that impact their choices and satisfaction when visiting coffee shops. This study seeks to shed light on these issues and their implications for coffee shop owners and marketers in Kelantan. The authors collected data from 154 young individuals in Kota Bharu, Kelantan, through an online survey questionnaire using non-probability sampling techniques. Our findings reveal a strong connection between young generations' perception of service quality, value, and satisfaction, which act as important factors in shaping their behavioural intentions to patronize the coffee shop. This research provides valuable insights and data for coffee shop businesses in Kota Bharu, Kelantan, helping them enhance their service quality, improve the value they offer, and cater to the preferences of their target market. By understanding the perceptions and preferences of younger generations, businesses can better meet their needs, increase young generation’s satisfaction, and build loyalty. Our study emphasizes the significance of providing excellent service quality and value to achieve young generation’s satisfaction and foster positive behavioral intentions towards coffee shops. These insights can assist coffee shop businesses in developing effective strategies to attract and retain young generations, ultimately contributing to their long-term success and profitability.